2011
DOI: 10.1212/wnl.0b013e318237f660
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MuSK autoantibodies block binding of collagen Q to MuSK

Abstract: Objective: Muscle-specific receptor tyrosine kinase (MuSK) antibody-positive myasthenia gravis (MG) accounts for 5%-15% of autoimmune MG. MuSK mediates the agrin-signaling pathway and also anchors the collagenic tail subunit (ColQ) of acetylcholinesterase (AChE). The exact molecular target of MuSK-immunoglobulin G (IgG), however, remains elusive. As acetylcholine receptor (AChR) deficiency is typically mild and as cholinesterase inhibitors are generally ineffective, we asked if MuSK-IgG interferes with binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 37 publications
6
126
0
Order By: Relevance
“…Animal experiments show that MuSK immunoglobulin G (IgG) can cause MG. Mice that received repeated daily injections of patient IgG showed impaired neuromuscular transmission, with reductions in endplate AChR [18][19][20]. Similar changes to endplates were reported in mice, rats, and rabbits that were actively immunized with MuSK [21,22].…”
Section: Krisnamurti Et Alsupporting
confidence: 69%
“…Animal experiments show that MuSK immunoglobulin G (IgG) can cause MG. Mice that received repeated daily injections of patient IgG showed impaired neuromuscular transmission, with reductions in endplate AChR [18][19][20]. Similar changes to endplates were reported in mice, rats, and rabbits that were actively immunized with MuSK [21,22].…”
Section: Krisnamurti Et Alsupporting
confidence: 69%
“…Five patients harbored additional reactivity against the Ig-like domain 2 in the ELISA. Others have reported that patients harbor autoantibodies outside of the Ig-like domains, including the Frizzled-like domain (13,34,35). These differences might be caused by racial differences and/or different disease states of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…As such, antibodies that inhibit MuSK function would be expected to disrupt the architecture of the neuromuscular synapse as well as perturb neurotransmitter release and reception (9,18,19,34,(41)(42)(43)(44). Because the synaptic accumulation of acetylcholinesterase (AChE), like all other postsynaptic proteins, depends on MuSK (10,42), IgG4 antibodies to MuSK are likely to lower AChE expression at the synapse, which may explain the hypersensitivity of MuSK MG patients to AChE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The MuSK protein, which is located at the postsynaptic membrane, anchors the C-terminal portion of collagen Q (ColQ), which binds acetylcholinesterase (AChE) at the N terminal (14,15). AChE stabilization depends on its binding to ColQ (16).…”
Section: Discussionmentioning
confidence: 99%
“…AChE stabilization depends on its binding to ColQ (16). The anti-MuSK antibodies interfere with the MuSK-ColQ binding and reduce the AChE activity at the neuromuscular junction, resulting in an increased synaptic acetylcholine concentration (15). As a result, the MuSK antibodies may produce peripheral nerve hyperexcitability, which can cause muscular fasciculation activities (17).…”
Section: Discussionmentioning
confidence: 99%